Efektifitas Psikoedukasi Self Esteem Untuk Menurunkan Prokrastinasi Akademik pada Siswa SMK: Effectiveness of Self Esteem Psychoeducation to Reduce Academic Procrastination in Vocational High School Students - Muhammad Dzaky Royhan; Effy Wardati Maryam (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Academic procrastination remains a persistent behavioral problem among adolescents in vocational education, often associated with internal psychological factors. Specific Background: Low self-esteem has been identified as one of the internal determinants contributing to students’ tendency to delay academic tasks. Knowledge Gap: Although prior studies have examined the relationship between self-esteem and academic procrastination, limited experimental evidence evaluates structured psychoeducation focusing on self-esteem development in vocational high school settings. Aims: This study aims to examine the effectiveness of self-esteem psychoeducation in reducing academic procrastination among students of SMK Antartika 1 Sidoarjo. Results: Using a quantitative pre-experimental one group pretest-posttest design involving 40 eleventh-grade students, the paired sample t-test revealed a significant difference between pretest and posttest scores (p = 0.004), indicating a decrease in academic procrastination after the intervention. Novelty: This study provides empirical evidence of a structured self-esteem psychoeducation program implemented in a vocational high school context using a pre-experimental approach. Implications: The findings highlight the importance of integrating self-esteem development programs within school counseling services to address academic procrastination behaviors. Keywords: Self Esteem, Academic Procrastination, Psychoeducation, Vocational High School, Pre Experimental Design Key Findings Highlights: Statistical testing shows significant score differences before and after intervention. Structured sessions contribute to behavioral change within three weeks. Counseling-based programs demonstrate measurable student progress.